Development and characterization of a hydrogel-based adhesive patch for sealing open-globe injuries. (1st January 2022) - Jumelle, Clotilde; Yung, Ann; Sani, Ehsan Shirzaei; Taketani, Yukako; Gantin, Fanny; Bourel, Louisa; Wang, Shudan; Yüksel, Erdem; Seneca, Senne; Annabi, Nasim; Dana, Reza
Abstract: Full-thickness wounds to the eye can lead to serious vision impairment. Current standards of care (from suturing to tissue transplantation) usually require highly skilled surgeons and use of an operating theater. In this study, we report the synthesis, optimization, and in vitro and ex vivo testing of photocrosslinkable hydrogel-based adhesive patches that can easily be applied to globe injuries or corneal incisions. According to the type and concentration of polymers used in the adhesive formulations, we were able to finely tune the physical properties of the bioadhesive including viscosity, elastic modulus, extensibility, ultimate tensile strength, adhesion, transparency, water content, degradation time, and swellability. Our in vitro studies showed no sign of cytotoxicity of the hydrogels. Moreover, the hydrogel patches showed higher adhesion on freshly explanted pig eyeballs compared to a marketed ocular sealant. Finally, ex vivo feasibility studies showed that the hydrogel patches could seal complex open-globe injuries such as large incision, cruciform injury, and injury associated with tissue loss. These results suggest that our photocrosslinkable hydrogel patch could represent a promising solution for the sealing of open-globe injuries or surgical incisions. Statement of significance: Current management of severe ocular injuries require advanced surgical skills and access to an operating theater. To address the need for emergent management of wounds that cannot be handled in the operating room, surgical adhesives have gained popularity, but none of the currently available adhesives have optimal bioavailability, adhesive or mechanical properties. This study describes the development, optimization and testing of a light-sensitive adhesive patch that can easily be applied to the eye. After solidification using visible light, the patch shows no toxicity and is more adherent to the tissue than a marketed sealant. Thus this technology could represent a promising solution to stabilize ocular injuries in emergency settings before definitive surgical repair. Graphical abstract: Image, graphical abstract